#### notes

1) Substitution Method- Let us try to understand this method with a simple example

`x+y=8` .....eq1

`x-y=-2` ....eq2

As the name suggests we are required to substitute `x=8-y` in eq2

`8-y-y= -2`

`-2y= -2-8= -10`

`y=5` and `x+5=8`

Therefore `x=3`

If you would like to contribute notes or other learning material, please submit them using the button below.

#### Video Tutorials

#### Shaalaa.com | Pair of Linear Equation in two variable part 9 (Algebraic Substitution)

#### Related QuestionsVIEW ALL [6]

#### Related concepts

Advertisement